2018
DOI: 10.4028/www.scientific.net/kem.769.90
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Microwave and Electron Beam Irradiation on Composition of Aluminum Nanopowder

Abstract: The influence of microwave irradiation (9.4 GHz) and electron beam (250 keV) on metal aluminum content in aluminum nanopowder is studied. It is established that after irradiation the content of metal aluminum in Al nanopowder increases. The most likely explanation is the reduction of aluminum ions Al3+ in the oxide shell at the surface of aluminum nanoparticles to produce metal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In this regard, in order to simulate thermal processes in metal powders when exposed to microwave radiation, a mathematical apparatus was developed, which is described in detail in the works [ 10 , 14 ]. In addition, it was experimentally found that under the action of short-pulse microwave radiation, metal powders change their thermochemical properties [ 15 , 16 ]. The temperature at the beginning of the oxidation of aluminum powder decreases, the specific heat of oxidation increases, and the degree of oxidation when heated in air increases after exposure to microwave radiation with a frequency of 9.4 GHz and a power density of 80 W/cm 2 [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, in order to simulate thermal processes in metal powders when exposed to microwave radiation, a mathematical apparatus was developed, which is described in detail in the works [ 10 , 14 ]. In addition, it was experimentally found that under the action of short-pulse microwave radiation, metal powders change their thermochemical properties [ 15 , 16 ]. The temperature at the beginning of the oxidation of aluminum powder decreases, the specific heat of oxidation increases, and the degree of oxidation when heated in air increases after exposure to microwave radiation with a frequency of 9.4 GHz and a power density of 80 W/cm 2 [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was experimentally found that under the action of short-pulse microwave radiation, metal powders change their thermochemical properties [ 15 , 16 ]. The temperature at the beginning of the oxidation of aluminum powder decreases, the specific heat of oxidation increases, and the degree of oxidation when heated in air increases after exposure to microwave radiation with a frequency of 9.4 GHz and a power density of 80 W/cm 2 [ 15 ]. On the other hand, it was shown that with an increase in the duration of microwave pulses and irradiation time, the thermal heating and annealing of the protective oxide shell on the surface of aluminum particles occur, which leads to a decrease in the specific thermal effect of oxidation.…”
Section: Introductionmentioning
confidence: 99%